2017
DOI: 10.2174/1389202917666161102095508
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric Non-coding Transcription: Opening the Black Box of Chromosomal Instability?

Abstract: In eukaryotes, mitosis is tightly regulated to avoid the generation of numerical chromosome aberrations, or aneuploidies. The aneuploid phenotype is a consequence of chromosomal instability (CIN), i.e., an enhanced rate of chromosome segregation errors, which is frequently found in cancer cells and is associated with tumor aggressiveness and increased tumor cell survival potential. To avoid the generation of aneuploidies, cells rely on the spindle assembly checkpoint (SAC), a widely conserved mechanism that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Increasing study has reported that dysregulated lncRNAs were involved in the regulation of cancer progression. 17,18 A series of lncRNAs showed abnormal expressions in CC tissues, such as MNX1-AS1, HCP5, GAS5 and PVT1. [19][20][21][22] Also, SNHG7 was observed overexpressed in multiple cancer types and exhibited oncogenic roles in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing study has reported that dysregulated lncRNAs were involved in the regulation of cancer progression. 17,18 A series of lncRNAs showed abnormal expressions in CC tissues, such as MNX1-AS1, HCP5, GAS5 and PVT1. [19][20][21][22] Also, SNHG7 was observed overexpressed in multiple cancer types and exhibited oncogenic roles in multiple cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous non-coding RNAs that originated from centromeric and pericentromeric satDNAs have been discovered (Bouzinba-Segard et al 2006;Pezer & Ugarković 2008;Carone et al 2009;Rošić et al 2014) and these seem to be very important for centromeric function, as alterations in their transcriptional status were related to chromosome segregation errors in several eukaryotic species. Recent experimental evidence supports that a precise chromosome segregation is assured by the inhibition, degradation or overexpression of satellite DNAs (Eymery et al 2009;Gent & Dawe 2012;Ferreira et al 2015;Cáceres-Gutiérrez & Herrera 2017). Centromeric transcripts have been demonstrated to be essential for the deposition of CENP-A in human cells, as depletion of these transcripts leads to mitotic defects (Gent & Dawe 2012;Quénet & Dalal 2014).…”
Section: Contribution Of Satdna Transcription In Chromosomal Rearrangmentioning
confidence: 99%
“…It has been hypothesised that demethylation in certain DNA regions, including the pericentromeric satDNAs, assists the pericentromeric chromosomal rearrangements in lymphoblastoid cells incubated in vitro with DNA demethylating agents (Ji et al 1997). Additionally, several studies evidence that DNA demethylation of repetitive DNA might predispose cells to chromosomal rearrangements such as translocations, deletions and isochromosome formation (Narayan et al 1998;Ehrlich 2009;Tilman et al 2012;Ferreira et al 2015;Cáceres-Gutiérrez & Herrera 2017). It is thus possible that satDNA transcriptional regulation may constitute the missing piece to increase our understanding on the establishment of chromosomal instability, contributing to the occurrence of chromosomal rearrangements in the genome remodelling leading to Bovidae speciation.…”
Section: Contribution Of Satdna Transcription In Chromosomal Rearrangmentioning
confidence: 99%
“…The centromere is a chromosomal region that is required for chromosome segregation in mitosis [1]. The transcripts of this region, known as centromeric RNAs (cenRNAs), are thought to play a role in centromere function in several species [2][3][4][5]. Energetic studies on numerous types of protein factors that are involved in chromosome and kinetochore functions have been conducted.…”
mentioning
confidence: 99%
“…Prior investigations have revealed the roles of cenRNAs in CENP A loading [2,4,5,[7][8][9], association of CENP C to kinetochore [11], and CPC localization to centromeres in several species [3]. These properties are very important for identifying the centromeres.…”
mentioning
confidence: 99%